Whole genome deep sequencing analysis of viral quasispecies diversity and evolution in HBeAg seroconverters - Lin, Su-Ru (JHEP Rep, 2021)
BACKGROUND & AIMS: We aimed to investigate how viral quasispecies of the HBV whole genome evolves and diversifies in response to HBeAg seroconversion and viral control utilising next-generation sequencing (NGS). METHODS: Fifty HBeAg-positive chronic hepatitis B patients, including 18 treatment-naïve and 32 interferon (IFN)-treated individuals, were recruited. Serial HBV whole genomes in serum were analysed by NGS to determine sequence characteristics and viral quasispecies. RESULTS: HBV quasispecies diversity, measured by nucleotide diversity, was negatively correlated with viral load and hepatitis activity. Spontaneous HBeAg seroconverters exhibited significantly greater viral quasispecies diversity than treatment-naïve non-seroconverters from >1 year before seroconversion (0.0112 vs. 0.0060, p <0.01) to >1 year after seroconversion (0.0103 vs. 0.0068, p <0.01). IFN-induced HBeAg seroconverters tended to have higher viral genetic diversity than non-seroconverters along with treatment. Particularly, the IFN responders, defined as IFN-induced HBeAg seroconversion with low viraemia, exhibited significantly greater genetic diversity of whole HBV genome at 6 months post-IFN treatment than IFN non-responders (0.0148 vs. 0.0106, p = 0.048). Moreover, spontaneous HBeAg seroconverters and IFN responders exhibited significantly higher evolutionary rates and more intra-host single-nucleotide variants. Interestingly, in spontaneous HBeAg seroconverters and IFN responders, there were distinct evolutionary patterns in the HBV genome. CONCLUSIONS: Higher HBV quasispecies diversity is associated with spontaneous HBeAg seroconversion and IFN-induced HBeAg seroconversion with low viraemia, conferring a favourable clinical outcome. LAY SUMMARY: HBeAg seroconversion is a landmark in the natural history of chronic HBV infection. Using next-generation sequencing, we found that the nucleotide diversity of HBV was negatively correlated with viral load and hepatitis activity. Patients undergoing HBeAg seroconversion had more diverse HBV genomes and a faster viral evolution rate. Our findings suggest HBeAg seroconversion is driven by host selection pressure, likely immune selection pressure.